Pengembangan Bahan Ajar Berbasis Pemecahan Masalah untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik pada Mata Pelajaran PPKn Kelas IV - Putri Akhiriyani Siregar; Auffah Yumni; Safran Safran (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to develop problem-solving-based teaching materials to improve students' critical thinking skills in class IV PPKn subjects based on the fact that the use of teaching materials in each PPKn subject is rarely used because educators only rely on textbooks as a guide. And in improving students' critical thinking skills, teachers only use multiple choice tests in the textbook without asking students to create their own ideas from the knowledge they have obtained. This research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) but the focus of this research is limited to this stage Development just. Data collection techniques used were interviews, observation, questionnaires and documentation. The results obtained after the teaching materials were validated by 3 validator experts, namely material experts, obtained an average score of 89.3% with the "Very Eligible" criteria. The results of the media expert validation assessment obtained an average score of 94.3% with the criteria "Very Eligible". And the results of the linguist validation assessment obtained an average score of 82% with the criteria "Very Eligible". Meanwhile, the results of the teacher's assessment of problem-solving based teaching materials obtained an average score of 94.6% with the criteria "Very Appropriate". This shows that problem-solving based teaching materials are very suitable for use in the learning process to improve students' critical thinking abilities.